1994
DOI: 10.1007/bf00173043
|View full text |Cite
|
Sign up to set email alerts
|

Radioiodinated metaiodobenzylguanidine: a review of its biodistribution and pharmacokinetics, drug interactions, cytotoxicity and dosimetry

Abstract: Since the introduction of radioiodinated metaiodobenzylguanidine in 1980, considerable research has been performed, both in the chemical field and in medical sciences. However, despite the wide use of radioiodinated metaiodobenzylguanidine, knowledge about its pharmacology is still limited. This paper reviews the biodistribution and pharmacokinetics, drug interactions, cytotoxicity and dosimetry of radioiodinated metaiodobenzylguanidine. Iodine-131 metaiodobenzylguanidine therapy is in general well tolerated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(67 citation statements)
references
References 47 publications
1
65
0
1
Order By: Relevance
“…The oral administration routes caused a shift in the biodistribution, mainly into the intestine and liver (Figure 2 and Table 1), without affecting total body clearance. This, however, does not reflect first-pass metabolism as MIBG is metabolized only to a minor degree (Wafelman et al, 1994). Despite a relatively high exposure to the small intestine and liver, no ulceration or other histological damage were observed in these tissues or in the stomach at the MTD.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The oral administration routes caused a shift in the biodistribution, mainly into the intestine and liver (Figure 2 and Table 1), without affecting total body clearance. This, however, does not reflect first-pass metabolism as MIBG is metabolized only to a minor degree (Wafelman et al, 1994). Despite a relatively high exposure to the small intestine and liver, no ulceration or other histological damage were observed in these tissues or in the stomach at the MTD.…”
Section: Discussionmentioning
confidence: 88%
“…At each time point, four animals were used. Because MIBG is, at least in humans, metabolized to only a minor degree (Wafelman et al 1994), [ 125 l]MIBG levels could be determined by gamma-counting of 100 µl of blood, 100 µl of plasma, the kidneys, liver and about 2 cm of the small intestine (at 1 cm distance of the stomach and flushed by PBS), which were expressed as percentage of the injected dose per ml of plasma or gram tissue. MIBG retained by the total body was calculated by adding the counts of the remaining body, corrected by 10/9 for differences in counting efficiency, to the counts of the excised tissues and expressed as percentage of total dose.…”
Section: Biodistribution and Bioavailabilitymentioning
confidence: 99%
“…131 I-metaiodobenzylguanidine ( 131 I-MIBG) is a licensed systemic treatment for the palliation of patients with metastatic NETs. 131 I-MIBG is a guanethidine derivative, structurally similar to noradrenaline and thus is accumulated in tissues arising from neural crest cells (Wafelman et al, 1994). 131 I-MIBG is transported by vesicular monoamine proteins and is concentrated in intracellular storage vesicles (Kolby et al, 2003).…”
mentioning
confidence: 99%
“…The assumption that the biodistribution and pharmacokinetics of 131 I-mIBG is identical in subsequent administrations can be questioned, but is supported by observations in the literature (Wafelman et al, 1994;Vallabhajosula and Nikolopoulou, 2011). Accumulation in cells of mIBG occurs by two processes: a specific and saturable uptake, and a non-specific and unsaturable uptake (Vallabhajosula and Nikolopoulou, 2011) and according to Wafelman et al (1994), no saturation effects in the specific uptake have been observed for therapeutic doses of 131 I-mIBG.…”
Section: Discussionmentioning
confidence: 99%